Investigation of Myoelectrical Function of Shoulder Periarthicular Muscles during Closed Kinetic Chain Execises in Healthy Young Persons - Khosrow Khademi-Kalantari; Simin Berenji; Seddigheh Sadat Na'eimi; Mehri Ghasemi (University of Social Welfare and Rehabilitation Sciences, 2009)
Objective: The effect of surface stability on the magnitude of the shoulder periarthicular muscular activity has remained controversial. The aim of this study was to investigate the relation between the changes in surface stability and the intensity of the static electromyographic activity of the shoulder periarthicular muscles. Materials & Methods: In this quasi experimental study, 30 healthy persons were selected conveniently according to inclusive and exclusive criteria and the surface electromyographic activity of superior trapezious, inferior trapezious, seratus anterior, long head of biceps, teres major and posterior deltoid in dominant side muscles of them were recorded at rest, and during 10 seconds standing on hands at 6 randomly ordered push up test positions with varied surface stability. The root mean square of the middle 3 seconds of electromyography was used for comparison of the muscular activity among the applied positions. Then data were compared by analysis of variance (ANOVA) with repeated measures and Pearsonian Correlation Coefficient tests. Results: The intensity of muscular activity in the 3 positions where the more stable surface was used was higher in comparison with the positions where the surface was unstable. The significant differences were seen in all muscles (P<0.001) except in superior trapezius muscle (P=0.081). Conclusion: Increasing the instability of the supporting surface can not be used as a method for progressively increasing the strength of periarthicular shoulder muscles.